Efecto de una intervención educativa en el conocimiento sobre autocuidado puerperal en puérperas atendidas en maternidad Hospital Regional de Loreto Iquitos 2021 - Ruiz Saavedra, Evelyn Sharonn (2023)
The research problem was: ¿Will the educational intervention improve knowledge about puerperal self-care in puerperal women attended at the Maternity Service of the Regional Hospital of Loreto Iquitos 2021?. The objective was to determine the effect of an educational intervention on knowledge about puerperal self-care in puerperal women attended in the Maternity Service of the Regional Hospital of Loreto de Iquitos 2021. The method was quantitative, the quasi-experimental design type pre and post test, the population was made up of 520 puerperal women attended in the Maternity Service of the Regional Hospital of Iquitos, the sample was 30 postpartum women. The techniques were the interview and the educational session, and the instruments were the knowledge questionnaire on puerperal self-care (Cronbach's Alpha reliability of α = 0.93 and validity r= 0.95), and the educational intervention "Puerperal Self-care". The results show that in the knowledge about puerperal self-care before the educational intervention, 70.0% was deficient and later it decreased to 30%; while after the educational intervention 80.0% was good and only 20% was poor. The statistical test t of student for related groups (applied to the difference Pre test - Post test), determined significant results p-value = 0,000 less than α (0.05), which allowed accepting the research hypothesis: The educational intervention will produce changes significant statistics in the level of knowledge about puerperal self care in puerperal women attended in the Maternity Service of the Regional Hospital of Loreto Iquitos 2021. Conclusion the Educational Intervention on "Puerperal self-care" was effective.